Stock Price Volatility in a Multiple Security Overlapping Generations Model - Spiegel, Matthew (Review of Financial Studies, 1998)
A number of empirical studies have reached the conclusion that stock price volatility cannot be fully explained within the standard dividend discount model. This article proposes a resolution based upon a model that contains both a random supply of risky assets and finitely lived agents who trade in a multiple security environment. As the analysis shows there exist 2^K equilibria when K securities trade. The low volatility equilibria have properties analogous to those found in the infinitely lived agent models of Campbell and Kyle (1991) and Wang (1993, 1994). In contrast, the high-volatility equilibria have very different characteristics. Within the high-volatility equilibria very large price variances can be generated with very small supply shocks. Adding securities to the economy further reduces the required supply shocks. Using previously established empirical results the model can reconcile the data with supply shocks that are less than 10% as large as observed return shocks. These results are shown to hold even when the dividend process is mean reverting.